Effectiveness of surfactants for unique hierarchical Mn2O3 nanomaterials as enhanced oxidative catalysts, antibacterial agents, and photocatalysts. (September 2020) - Amsaveni, P.; Nivetha, A.; Sakthivel, C.; Suresh Philip, C.; Prabha, I.
Abstract: We present the chemical-surfactant-mediated and green-surfactant-mediated synthesis of manganese (III) oxide nanoparticles prepared by the precipitation method using cetyltrimethylammonium bromide and tea extract, respectively, and their structural and optical properties. The nanoparticles were characterized by X-ray diffraction, scanning electron microscopy–energy-dispersive X-ray analysis, UV–Vis spectroscopy, and Fourier transform IR spectroscopy with regard to the diffraction pattern, phase, size, shape, composition of material, etc. The Mn2 O3 nanoparticles had an orthorhombic structure with crystallite sizes of 25.96 and 13.17 nm for chemical synthesis and green synthesis, respectively. The chemically synthesized Mn2 O3 nanoparticles were cubic and the green-synthesized Mn2 O3 nanoparticles were spherical, with average particle sizes of 30–50 nm and 20–40 nm, respectively, and band gaps of 2.2 and 2.1 eV, respectively. The photodegradation of methylene blue was analyzed with Mn2 O3 nanoparticles under solar irradiation. The present study also revealed the catalytic ability for oxidation reaction and the antimicrobial activities of the chemically synthesized and green-synthesized Mn2 O3 nanoparticles, and their effectiveness was compared. Graphical abstract: Image 1 Highlights: Manganese(III) oxide is synthesized with manganese acetate tetrahydrate as a precursor. The green-surfactant-assisted precipitation method uses chemical-free tea grain extract as a surfactant. The efficiency and properties of the green-synthesized and chemically synthesized nanoparticles are compared. The nanoparticles have well-defined cubic and spherical shapes with sizes of 20–50 nm. Antimicrobial activity, oxidative transformation, and removal of pollutants from water by photodegradation are studied.